The Effect of Chronic Inhouse Biomass Fuel Smoke Exposure on Coronary Slow Flow Phenomenon in Women Living in the Eastern Region of Turkey - Tayyar AKBULUT; Faysal SAYLIK (Medeniyet Medical Journal)
Objective: Biomass fuel (BMF) is still widely used in rural areas for cooking and heating worldwide. BMF smoke inhalation is a prominent cause of respiratory and cardiovascular disease. The slow coronary flow (SCF) phenomenon is known as the delayed opacification of distal coronary arteries on a coronary angiogram. SCF is known to be related to cardiovascular morbidity and mortality. Thus, we aimed to investigate the relationship between exposure to BMF and SCF in women in this study. Methods: A total of 457 consecutive women who underwent coronary angiography were retrospectively enrolled in this study. Patients were divided into two groups according to the use of BMF during their lives, from birth to older ages, as biomass exposure group (BEG) and non-exposure group. The presence of SCF was calculated based on thrombolysis in myocardial infarction frame count. Results: Two hundred fifty nine patients were in the BEG, whereas 198 patients were in the non-exposure group. The prevalence of SCF was higher in the BEG compared to the non-exposure group (47.9% vs. 13.1%, respectively, p<0.001). The presence of biomass exposure, body mass index, white blood cell count, low-density lipoprotein cholesterol, C-reactive protein, serum creatinine, and hypertension were independent predictors of SCF. The optimal cutoff point of biomass exposure time in years to detect the presence of SCF was 30 years (Area under the curve: 0.71, sensitivity: 0.65, specifity: 0.71). Conclusions: Exposure to indoor BMF was associated with a SCF phenomenon in women.